Xây dựng mô hình thử nghiệm thống kê đa biến nhận biết ung thư đại trực tràng dựa trên dữ liệu phổ NMR mẫu nước tiểu - Tài, Nguyễn Tiến; Kim Ngọc, Vũ Thị; Thái, Vũ Hùng; Tụ, Lê Thành; Tâm, Nguyễn Quang (Vietnam Journal of Chemistry, 2015)
Statistical models for Colorectal Cancer (CRC) identification were built by metabolomics, based on the 1H NMR data of urine and used statistical multivariate analysis (MVA) tools, named principle component analysis (PCA) and partial least square (PLS). Demonstration of PCA and PLS application on urine NMR data of 17 cases and 41 controls collected at MEDIC centre (HoChiMinh city) showed remarkable differences between CRC cases and controls; Tryptophan and Glutamate were profiled as metabolic CRC markers.